The Power Threat Meaning Framework and the Climate and Ecological Crises - Morgan, Gareth; Barnwell, Garret; Johnstone, Lucy; Shukla, Kirsten; Mitchell, Annie (PINS-Psychology in Society, 2022)
Climate change poses an existential threat to today’s and future generations. Within this context, important debates are taking place about the risk of individualising and de-contextualising both climate-related distress and denial. Seeking to re-centre context and power, we tentatively share our thoughts on how the Power Threat Meaning Framework (PTMF) might provide a useful lens to understand different responses to climate change. The paper draws on existing research, theory and experiences to elaborate on the domains of the PTMF, which include Power, Threat, Meaning, Threat Responses and Strengths. We focus on ideological and ecological power, with the latter proposed as a new aspect of power to be considered for future iterations of the PTMF. We illustrate how the different domains of the PTMF can be brought together to generate meta-narratives by offering a climate trauma pattern. We hope this article will be of use to activists, academics and professionals in supporting non-pathologising understandings of different reactions to climate breakdown while also suggesting ways to move forward.